Economic development for Eastern Europe : proceedings of a conference held by the International Economic Association - Kaser, Michael Charles; International Economic Association (London ; Melbourne [etc.] ; New York : Macmillan ; St. Martin's Press, 1968)
This volume is a collection of papers and a report of the debate which took place at the Conference on Economic Development for Eastern Europe (Plovdiv, Bulgaria, December 1964). The papers were contributed by East European economists while the discussions were based on the views expressed by eminent Eastern and Western scholars. The discussions covered diverse subjects ranging from the price system, strategy for growth, foreign trade and agriculture to mathematical models for economic take-off
Held December, 1964 in Plovdiv, Bulgaria.
Bibliographical footnotes.
lje 23/10/18
Loans
Keywords: Economic development; Economic ggrowth; Europe, Eastern